Library metrics – studying academic users' information retrieval behavior: A case study of an Israeli university library. (December 2017) - Greenberg, Riki; Bar-Ilan, Judit
The purpose of this study is to get insights on library users' information retrieval behavior, as reflected in log files, reports, and publishers' counts. From the data it appears that the library's discovery tool is not the major source for accessing full text items and the patrons often prefer other sources such as Google Scholar. Google Scholar cannot replace the library, but it can link users to resources that the patrons can access, through library subscriptions.